Bilateral Jugular Vein and Sigmoid Sinus Thrombosis Related to an Inherited Coagulopathy: An Unusual Presentation. (21st August 2014) - Altıntaş, Özge; Gürsoy, Azize Esra; Baran, Gözde; Mehdi, Elnur; Asil, Talip
Abstract : Internal jugular vein thrombosis (IJVT) is a rare condition associated with malignancy, coagulopathy, and trauma. The optimal management of any IJVT must be individualized and depends on the condition of the patient. Case Presentation. We report the case of a 42-year-old woman with a history of a first trimester spontaneous abortion. Apart from a tension-type headache, she had no neurological symptoms. She reported an incidental diagnosis of right-sided IJVT when she was evaluated for hyperthyroidism ultrasonographically. On ultrasonography, we observed bilateral jugular vein thrombosis. The patient was started on oral warfarin. Seven months later, when she was adequately anticoagulated, she developed a second thrombosis. According to the etiological workup, she had a mutation in the homozygous methylene tetrahydrofolate reductase ( MTHFR ) gene and reduced protein C levels and activity. Conclusion. This report illustrates an unusual presentation of a rare condition. In this case, the etiology was associated with the coagulopathy, which occurred despite adequate anticoagulation.